Inteligência artificial em hospitais do Rio Grande do Sul proposição de um framework para criação de valor - Berti, Christiano dos Santos (Universidade do Vale do Rio dos Sinos, 2021)
This study aims to suggest a framework for value creation using companies that provide solutions in Artificial Intelligence for hospitals in Rio Grande do Sul. Based on the Design Science Research methodology, 14 interviews were conducted with managers and patients of the hospitals Moinhos de Vento and São Lucas of the Pontifícia Universidade Católica do Rio Grande do Sul and with market experts that resulted in the identification of hospital problems. Furthermore, 5 classes of problems were identified that supported the search in the academic literature for frameworks with the purpose of solving the identified problems. Sixteen artifacts with this potential were listed, and, through an evaluation system, 4 are classified for artifact analysis with greater adherence in an exploratory focus group formed by 4 businesses consultants. The framework is then developed through the focus group feedbacks and the recommendation of merging 4 artifacts. Afterwards, the final version of the framework is successfully evaluated by the board of directors of the São Lucas Hospital of the Pontifícia Universidade Católica do Rio Grande do Sul. Finally, 8 lessons learned from the study and 9 managerial implications regarding the applicability of the framework are pointed out.
Keywords: Hospital; Inteligência artificial; Framework; Criação de valor; Design science research; Artificial intelligence; Value creation; ACCNPQ::Ciências Sociais Aplicadas::Administração